Estudo dos comportamentos e riscos nos infectados pelo VIH com e sem coinfecção pelo VHB e/ou VHC - Rodrigues, Francisco José Barbas (2006)
In this work we had as the main purpose the population’s characteristics study, their behaviours and the risks of the HIV bearers, with or without co-infection by HBV and/or HCV. According to our work and doing a small introduction to each one of the viruses, it was first made a bibliographical revision with the purpose of the evaluation of the science state, falling back upon reference works. They were done surveys to 95 individuals, all coming of the external consultation of infectology from the Joaquim Urbano Hospital - Porto, who were distributed in two groups. The group I was constituted by HIV bearers, with or without co-infection by HBV and/or HCV and the group II, of control, included bearers of HBV, HCV or HBV and HCV. Sixty six elements were integrated in the group I and the remaining ones in the group II. The sample was predominantly constituted by elements of the masculine gender (82,1%) and most (66,7%) interfered in the age group between 26 and 39 years old. In what concerns the scholarship 55,8% just stopped the basic teaching. 66,3% are or were already toxic dependents by intravenous, being, most (96,8%) consumers more than two years and still 68,3% refer the share of needles and syringes during the drugs consumption by intravenous way. According to the pathology, 5,3% were infected by HBV, 20% by HCV and 32,6% by HIV. In the remaining cases, 5,3% presented coinfection by HBV/HCV, 4,2% by HBV/HIV, 26,3% were bearers of HCV and HIV, 6,3% were simultaneously infected by HBV, HCV and HIV, had most of them (81,1%) been diagnosed for more than two years. According to the infection acquisition way, we recorded a balance among the ones who say that they have been infected due to the use of drugs by intravenous and the ones who refer the sexual relations as the cause of their pathology. Both of these acquirements forms corresponded mostly to the answers. Bearers of B hepatitis had a tendency to associate their infection to sexual relations, bearers of HCV, there was a balance among the ones who refer the use of drugs as the cause and the ones who don't know the infection cause and among the HIV bearers most of them pointed the sexual relations as the probable cause of the virus acquisition. When co-infection of HIV exists with one or two hepatotropic virus, there was a major individuals' tendency to associate the pathology to the drugs. The bearers of HBV and HCV also pointed the similar reason.